Report of the Committee for Programme and Coordination - United Nations Department for General Assembly; Conference Management (United Nations)
The Committee for Programme and Coordination held its organizational session (1st meeting) on 28 April 2011 and its substantive session from 6 June to 1 July 2011 at United Nations Headquarters. It held a total of 10 meetings and some 20 informal consultations, which tackles selection of reports of the Joint Inspection Unit, election of officers, and the adoption of the report of the Committee.